2015
DOI: 10.1007/s13562-015-0310-1
|View full text |Cite
|
Sign up to set email alerts
|

Metageographic population analysis of Colletotrichum truncatum associated with chili fruit rot and other hosts using ITS region nucleotide sequences

Abstract: Colletotrichum truncatum is one of the most economically important fungal pathogen causing anthracnose disease in pre and post-harvest stages of many crops worldwide. Little information is available in the literature on the genetic analysis and demographic history of this fungal pathogen. In the present study nucleotide sequence data of internal transcribed spacer (ITS) region were analyzed for C. truncatum isolates infecting chili and other crops worldwide to determine a metageographic pattern of distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Because of the obvious implications of this epidemiological hypothesis, further studies should be conducted to elucidate this aspect. Information on the levels of genetic diversity among C. truncatum populations from distinct hosts and countries could contribute to elaborate effective management strategies based on host resistance (Katoch et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the obvious implications of this epidemiological hypothesis, further studies should be conducted to elucidate this aspect. Information on the levels of genetic diversity among C. truncatum populations from distinct hosts and countries could contribute to elaborate effective management strategies based on host resistance (Katoch et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, comparison of multiple nucleotide sequences, such as the nuclear rDNA internal transcribed spacer (ITS) region, b-tubulin (TUB2), actin (ACT), glutamine synthetase (GS) and glyceraldehyde 3-phosphate dehydrogenase (GAPDH), have provided substantial information regarding the phylogenetic relationship among individuals and the genetic structure of the population (Rampersad et al, 2013). Previous reports have suggested the usefulness of a polyphasic approach to determine the greatest variability among closely related Colletotrichum species (Cai et al, 2009) and even among individuals of the same species (Katoch et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, domestication, introduction, and continuous cultivation of host plants of B. sorokiniana could be the plausible explanation for topical population expansion in different wheat growing zones of India. Such type of fungal population movement has been documented in different types of fungal pathogens (Kashyap et al 2020b;Dietzel et al 2019;Katoch et al 2016;Linde et al 2010;Zaffarano et al 2008).…”
Section: Discussionmentioning
confidence: 94%
“…A large number of studies have revealed the signi cance of internal transcribed spacer (ITS) region (a nuclear rDNA repeat unit) in resolving their fungal taxonomic status at the genus and species level (Kashyap et al 2017;Zhang et al 2017;Kashyap et al 2016;Katoch et al 2016;Rai et al 2016;Nilsson et al 2009;Wickert et al 2012). Glass and Donaldson (1995) reported high rate of evolution in ITS1 and ITS2 spacers and provided strong evidence for their deployment as an evolutionary marker for dissecting inter-and intra-speci c variations.…”
Section: Introductionmentioning
confidence: 99%